Correction: Synthesis of vinyl-substituted alcohols using acetylene as a C2 building block. Issue 7 (6th February 2023) - Lin, Zhicong; Liu, Boxiang; Wang, Yu; Li, Siju; Zhu, Shifa
Abstract : Correction for 'Synthesis of vinyl-substituted alcohols using acetylene as a C2 building block' by Zhicong Lin et al., Chem. Sci., 2023, ; https://doi.org/10.1039/d2sc06400f .